Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 120025 by mathmax by abdo last updated on 28/Oct/20

calculate f^′ (x)  1) f(x) =∫_0 ^∞   ((cos(xt))/(t^2 +x^2 ))dt  2)f(x)=∫_0 ^∞   ((sin(xt^2 +(√2)))/(t^2 +x^2  +3))dt

calculatef(x)1)f(x)=0cos(xt)t2+x2dt2)f(x)=0sin(xt2+2)t2+x2+3dt

Answered by Bird last updated on 29/Oct/20

1)f(x)=_(t=xu)   ∫_0 ^∞  ((cos(x^2 u))/(x^2 (u^2 +1)))xdu  =(1/x)∫_0 ^∞   ((cos(x^2 u))/(u^2 +1))du   (we tske x>0)  =(1/(2x)) Re(∫_(−∞) ^∞   (e^(ix^2 u) /(u^2 +1))du)  ∫_(−∞) ^∞  (e^(ix^2 z) /(z^2 +1))dz =2iπ Res(f,i)  f(z)=(e^(ix^2 z) /((z−i)(z+i))) ⇒Res(f,i)=(e^(−x^2 ) /(2i))  ⇒∫_(−∞) ^(+∞)  (e^(ix^2 z) /(z^2 +1))dz =2iπ.(e^(−x^2 ) /(2i))  =π e^(−x^2 )  ⇒f(x) =(π/(2x))e^(−x^2 )  ⇒  f^′ (x) =(π/2){−(1/x^2 )e^(−x^2 ) +(1/x)(−2x)e^(−x^2 ) }  =(π/2){−(1/x^2 )e^(−x^2 ) −2e^(−x^2 ) }  =−(π/2){(1/x^2 )+2}e^(−x^2 )   =−π×((1+2x^2 )/(2x^2 )) e^(−x^2 )

1)f(x)=t=xu0cos(x2u)x2(u2+1)xdu=1x0cos(x2u)u2+1du(wetskex>0)=12xRe(eix2uu2+1du)eix2zz2+1dz=2iπRes(f,i)f(z)=eix2z(zi)(z+i)Res(f,i)=ex22i+eix2zz2+1dz=2iπ.ex22i=πex2f(x)=π2xex2f(x)=π2{1x2ex2+1x(2x)ex2}=π2{1x2ex22ex2}=π2{1x2+2}ex2=π×1+2x22x2ex2

Answered by Bird last updated on 29/Oct/20

2)f(x)=∫_0 ^∞  ((sin(xt^2 +(√2)))/(t^2 +x^2 +3))dt ⇒  f(x)=(1/2)∫_(−∞) ^(+∞)  ((sin(xt^2 +(√2)))/(t^2 +x^2  +3))dt  =(1/2)Im(∫_(−∞) ^(+∞)  (e^(i(xt^2 +(√2))) /(t^2 +x^2 +3))dt)  g(z)=(e^(i(xz^2 +(√2))) /(z^2 +x^2 +3)) ⇒  g(z) =(e^(i(xz^2 +(√2))) /((z−i(√(x^2 +3)))(z+i(√(x^2 +3)))))  ∫_(−∞) ^(+∞) g(x)dz =2iπ Res(g,i(√(x^2 +3)))  =2iπ×(e^(i(x(−x^2 −3)+(√2))) /(2i(√(x^2 +3))))  =(π/( (√(x^2 +3)))).e^(i(−x^3 −3x+(√2)))   =(π/( (√(x^2 +3)))){cos(−x^3 −3x+(√2))  +isin(−x^3 −3x+(√2))} ⇒  f(x)=(π/(2(√(x^2 +3))))sin(−x^3 −3x+(√2))  =−(π/(2(√(x^2 +3))))sin(x^3 +3x−(√2))  f(x)=−(π/2)(x^2 +3)^(−(1/2)) sin(x^3 +3x−(√2)) ⇒  f^′ (x)=−(π/2){−x(x^2 +3)^(−(3/2)) sin(x^3 +3x−(√2))+(x^2 +3)^(−(1/2)) (3x^2 +3)cos(x^3 +3x−(√2))}  f^′ (x) =−(π/2){−(x/((x^2 +3)(√(x^2 +3))))sin(x^3 +3x−(√2))+((3x^2 +3)/( (√(x^2 +3))))cos(x^3 +3x+(√2))}

2)f(x)=0sin(xt2+2)t2+x2+3dtf(x)=12+sin(xt2+2)t2+x2+3dt=12Im(+ei(xt2+2)t2+x2+3dt)g(z)=ei(xz2+2)z2+x2+3g(z)=ei(xz2+2)(zix2+3)(z+ix2+3)+g(x)dz=2iπRes(g,ix2+3)=2iπ×ei(x(x23)+2)2ix2+3=πx2+3.ei(x33x+2)=πx2+3{cos(x33x+2)+isin(x33x+2)}f(x)=π2x2+3sin(x33x+2)=π2x2+3sin(x3+3x2)f(x)=π2(x2+3)12sin(x3+3x2)f(x)=π2{x(x2+3)32sin(x3+3x2)+(x2+3)12(3x2+3)cos(x3+3x2)}f(x)=π2{x(x2+3)x2+3sin(x3+3x2)+3x2+3x2+3cos(x3+3x+2)}

Terms of Service

Privacy Policy

Contact: info@tinkutara.com